PERILAKU KONSUMTIF DIKALANGAN MAHASISWA - Nur Komala, Eny; Rifa'i (JURNAL ILMIAH IDEA, 2026)
This study raises one problem, namely how consumptive behavior among Social Sciences students at the Muhammadiyah University of Bengkulu. This type of research is descriptive qualitative, using several informants in conducting interviews and observations by means of purposive sampling. The data source used is primary data, namely information that comes from direct observation at the research location after conducting observations and interviews. Meanwhile, secondary sources are data obtained from documentation or literature studies to complement primary data. Data collection was carried out by field research through observation, interviews, and documentation. The results of this study indicate that more students tend to behave consumptively based on the three forms of consumptive behavior of students around the UMB campus, namely in terms of food, shopping for "fashion" appearance needs, ways to fill free time such as shopping malls, and others. The factors that cause consumptive behavior in students are the influence of lifestyles that follow current trends, the influence of the social environment, the number of shopping centers, and joining in.